Variable Raindrop Size Distributions in Different Rainbands Associated With Typhoon Fitow (2013). Issue 22 (25th November 2019) - Bao, Xuwei; Wu, Liguang; Tang, Bi; Ma, Leiming; Wu, Dan; Tang, Jie; Chen, Haojun; Wu, Lianyao
Abstract: The microphysical characteristics of rain may vary in different rain regions of a tropical cyclone (TC), but few studies have demonstrated the differences in raindrop size distributions (RSDs) of convective rain in different rainbands of a specific TC. This study examines the RSD characteristics and evolution of convective rain within outer rainbands and a coastal‐front‐like rainband associated with Typhoon Fitow, based on observational data from a disdrometer at Shibo station in Shanghai, China, during 6–7 October 2013. Considering the fast passage of convective TC rainbands over the disdrometer and the low rain rate of stratiform rain in the outer area, this study proposes a modified rain‐type classification method based on the disdrometer data. This study indicates that convective outer‐rainband rain (ORR) and coastal‐front rain (CFR) have different rain parameters, three parameters of the gamma model, radar reflectivity–rain rate ( Z ‐ R ), and shape–slope ( μ ‐ Λ ) relationships. The convective ORR has higher concentrations at all drop sizes than the convective CFR as well as larger spectral width, leading to the greater rainfall rate. The different Z ‐ R relationships suggest the necessity of a variable relationship for quantitative precipitation estimation (QPE) in different rain regions of the TC. This study also demonstrates for the first time that the RSD evolution with increasing rain rate is different in various convective rainbands associated with Fitow, suggesting that different microphysical parameterization schemes may be required for different rainbands in TC models. Key Points: variable RSDs in different rainbands associated with Typhoon Fitow different Z‐R relationships in different rain regions outwards from the TC center different evolution of RSDs in different convective TC rainbands with increasing rain rate